ANALYSIS OF THE FACTORS THAT INFLUENCE EMPLOYMENT AS ONLINE TRANSPORTATION DRIVERS IN BATAM CITY - Evi Silvana Muchsinati; Marcerllina Teo (Journal of Business Studies and Management Review, 2021)
The development of transportation always follows by technological developments. The impact given by changes in technological developments on online transportation is to provide opportunities for people to have new jobs. This research aims to analyze the influence of training, motivation, job stress, and job satisfaction on employee performance with employee engagement as a mediation. This study involves 400 employees of Gojek in Batam City. Using SmartPLS analysis, it was found that training is positive not significant on employee performance with employee engagement as mediation. Job stress is negative not significant on employee performance with employee engagement as mediation. Both motivation and job satisfaction has the most important role to enhance employee performance with employee engagement as mediation.